Allelopathy and its application as a weed management tool: A review - Khamare, Yuvraj; Chen, Jianjun; Marble, Stephen Christopher (Frontiers in Plant Science, 2022)
Weeds are a serious threat to crop production as they interfere with the crop growth and development and result in significant crop losses. Weeds actually cause yield loss higher than any other pest in crop production. As a result, synthetic herbicides have been widely used for weed management. Heavy usage of synthetic herbicides, however, has resulted in public concerns over the impact of herbicides on human health and the environment. Due to various environmental and health issues associated with synthetic herbicides, researchers have been exploring alternative environmentally friendly means of controlling weed. Among them, incorporating allelopathy as a tool in an integrated weed management plan could meaningfully bring down herbicide application. Allelopathy is a biological phenomenon of chemical interaction between plants, and this phenomenon has great potential to be used as an effective and environmentally friendly tool for weed management in field crops. In field crops, allelopathy can be applied through intercropping, crop rotation, cover crops, mulching and allelopathic water extracts to manage weeds. Accumulating evidence indicates that some plant species possess potent allelochemicals that have great potential to be the ecofriendly natural herbicides. This review is intended to provide an overview of several allelopathic species that release some form of the potent allelochemical with the potential of being used in conventional or organic agriculture. Further, the review also highlights potential ways allelopathy could be utilized in conventional or organic agriculture and identify future research needs and prospects. It is anticipated that the phenomenon of allelopathy will be further explored as a weed management tool, and it can be a part of a sustainable, ecological, and integrated weed management system.